ASAS TIADA PIDANA TANPA KESALAHAN (ASAS KESALAHAN) DALAM HUBUNGANNYA DENGAN PERTANGGUNGJAWABAN PIDANA KORPORASI - Wirajaya, A. A. Ngurah; A. Martana, Nyoman (Kertha Negara : Journal Ilmu Hukum, 2013)
The principle of criminal nothing without fault or principle of fault is a fundamentalprinciple in criminal law and became one element of criminal responsibility of a subject ofcriminal law.The position of the corporation as a legal subject invites polemic associatedwith the existence of the principle of criminal nothing without fault in criminal responsibilityagainst corporate. Corporations do not have souls like human beings and not fulfillingelements ofa psychic can be said to have faults. Accordingly, this paper will be explain theexistence ofthe principle of fault as one element that must be met the legal subject may beliable as well as the influence of the principle of criminal nothing without fault in corporatecriminal responsibility.
Keywords: principle of fault, criminal responsibility, corporation